Farmer’s perspective in management of dystocia: A life threatening condition in cattle - J, Arunpandian; Kujur, Anju; M, Ganesan; N, Srivastava (Indian Farming, 2021)
Dystocia is a major, often a life threatening reproductive disorder in cattle and buffaloes. Moreover, since incidences of dystocia are severe drain on the resources a dairy farmer must undertake all preventive measures as explained above to optimize his income from dairy animals. This article aims to equip dairy farmers with awareness and possible aberration during normal calvings. Article outlines importance of early treatment, diagnosis, preventive measures, and nuances of first-aid to be administered by the farmer or a para-veterinarian in cases of dystocia in cows before a veterinarian arrives.